The needs of mothers of children with autism spectrum disorder (ASD) in the Kingdom of Saudi Arabia (KSA): a qualitative study - Hemdi, A.; Daley, David (2017)
The purpose of this qualitative study was to explore the unmet needs and experiences of mothers of ASD children in The Kingdom of Saudi Arabia (KSA). This study employed telephone interviews with eight Saudi mothers raising a child with autism. Questions from a researcher-developed interview guide elicited responses about challenges and unmet needs. Results indicated that the majority of respondents felt they had low to no knowledge of ASD prior to and after their child's diagnosis. Six themes were identified: i) Mothers’ identification of their lack of information about their children with ASD, ii) Mother’s perceptions about their mental and physical well-being, iii) Mothers’ recognition of their constant challenges raising children with ASD,iv) Suggestions to increase public awareness about ASD, v) Mothers’ identification of their training needs, and vi) Mothers’ perceptions of their children’s educational needs . Respondents insisted that cultural issues such as lack of transportation and fathers’ involvement did add to their burden. This study recommended that professionals and academics in KSA should take into consideration the unmet needs of mothers of ASD children when designing interventions and services for children with ASD to ensure they are tailored to the cultural context and needs of mothers.